DOES PERCEPTION OF WORK STRESS AND JOB SATISFACTION PREDICT BEING GENERATION X OR Y? SAMPLE OF PARTICIPATION BANKS IN TURKEY - Tunçbilek, Mehmet Murat; Sucu, Ubeydullah (International Journal of Contemporary Economics and Administrative Sciences, 2020)
According to literature, in a situation where Generation X is satisfied, Generation Y may not be. If there are differences in expectation and stress sources between generations as explained in the theory, it can also be expected to guess correctly whether one is Generation X or Y via these differences. This research has been conducted in order to test the thesis mentioned above. The scope of the research is the Head Office and Istanbul branches of Participation Banks. In total, 392 people participated in the research. The data acquired from the sample was analyzed through logistic regression method. Job satisfaction scale is Minnesota Job Satisfaction Scale. Both work stress scale and indicative scale of Generations X and Y were obtained by referring to the descriptive information that takes place in the relevant literature. Because of the weak consistence between the logistic regression model and the research data, perception levels of work stress and job satisfaction cannot predict to be Generation X or Y significantly.